THU0029 Bactericidal/permeability-increasing protein downregulates the inflammatory response to pathogenic crystals in vitro and in vivo. (15th June 2017) - Scanu, A; Luisetto, R; Oliviero, F; Galozzi, P; Ramonda, R; Punzi, L
Abstract : Background: Bactericidal/permeability-increasing protein (BPI) is a cationic protein mainly produced by polymorphonuclear cells (PMN) which exerts an antimicrobial activity by damaging bacterial membranes and interacts with specific cell surface receptors, such as toll-like receptors (TLRs). BPI has been detected in synovial fluid of patients with different arthritis, including crystal-induced arthritis. Objectives: To evaluate the effects and mechanisms of action of BPI in in vitro and in vivo models of crystal-induced inflammation. Methods: The human monocytic cell line THP-1 was primed for 3 h with phorbole myristate acetate (300 ng/ml), reincubated overnight, and treated with sterile synthetic monosodium urate (MSU) (0.5 mg/ml) or calcium pyrophosphate (CPP) (0.1 mg/ml) crystals for 24 h in presence or absence of BPI (5 μ g/ml). In some experiments, cells or crystals were pretreated with BPI for 2 h before stimulation. BPI inhibition experiments were carried out with antibody against TLR2 or TLR4. Cell supernatants were tested by ELISA for interleukin (IL)-1β and IL-8 production. Chemotactic effect of culture supernatants was evaluated in chemotaxis chamber by the migration of freshly isolated peripheral blood PMN. As regard the study in vivo, air pouches were raised on the backs of CD1 mice (n=7 per condition). 2 mg of MSU crystals in 1 ml of PBS were injected into the pouch in the presence or absence of 0.1 mg of BPI for 3 h. Controls received 1 ml of PBS. After the sacrifice, pouch fluids were recovered by washing with 2 ml of PBS. Leukocyte count in lavage fluids was obtained using a hemocytometer and the percentage of PMN was determined by May-Grünwald-Giemsa staining. IL-1β, chemokine (C-X-C motif) ligand 1 (CXCL1) and IL-6 levels were measured in exudates by ELISA. Results: Exposure of THP-1 cells to different types of crystals increased the production of IL-1β (MSU: 406.62±12.00 pg/ml; CPP: 357.07±25.17 pg/ml) and IL-8 (MSU: 3798.56±24.64 pg/ml; CPP: 3427.74±22.33 pg/ml). The release of both cytokines induced by crystals was significantly diminished in the presence of BPI (76% IL-1β, 58% IL-8), and tended to be more pronounced when cells, but not crystals, were pretreated with the protein (90% IL-1β, 65% IL-8). The presence of antibody anti-TLR2 or anti-TLR4 did not affect the BPI inhibitory effect. Supernatants of crystal-stimulated cells increased the migration of PMN cells which was reduced in the presence of BPI. The injection of MSU crystals into the subcutaneous pouches of mice induced leukocyte infiltration (10.2±3.39 x 10 5 cells/ml) comprising 68.6±8.75% of PMN. IL-1β (32.33±6.35 pg/ml), CXCL1 (467.07±27.47 pg/ml) and IL-6 (624.61±29.41 pg/ml) were measured in lavage fluids. The co-injection of MSU crystals and BPI inhibited leukocyte influx by 60% and PMN infiltration by 87% and, in turn, the levels of all assessed cytokines were reduced (81% IL-1β, 70% CXCL1, 35% IL-6). Conclusions: This study shows that BPI reduces the crystal-induced inflammatory process in vitro and in vivo by inhibiting pro-inflammatory cytokine release and PMN recruitment. The mechanism of action of BPI may include the direct interaction with activated cells in a TLR-independent manner. Disclosure of Interest: None declared